Detailed Structural Characterization of Arabinans and Galactans of 14 Apple Cultivars Before and After Cold Storage - Wefers, Daniel; Flörchinger, Ramona; Bunzel, Mirko (Frontiers in Plant Science, 2018)
Physiological and textural properties of apples are greatly influenced by both cultivar and structural composition of their pectic polysaccharides. In previous studies it was demonstrated that neutral pectic side chains (arabinans and galactans) play a major role during fruit development and postharvest processes. However, these complex polymers have a high structural heterogeneity, and some structural elements such as side chain substituents and substitution of neighboring residues cannot be analyzed by using conventional analytical methods. Therefore, fine structures of arabinans and galactans were analyzed in 14 apple cultivars before and after storage. Besides conventional methods such as methylation analysis, profiling approaches based on enzymatic cleavage were applied to obtain detailed information on the neutral side chains of pectins. Structurally different, highly branched arabinans and linear β-1,4-linked galactans were detected in all cultivars. By using enzymatic profiling approaches, rare structural elements such as β-arabinofuranose and α-arabinopyranose residues were detected. In addition, the combination of all methods indicated structural differences with regard to ramification position or patterns. Cold storage resulted in decreased portions of branched arabinans. It was demonstrated that arabinan decomposition is independent of previously detected structural variations. In addition, analysis of endo-arabinanase hydrolysates demonstrated that β-arabinofuranose containing side chains are enriched after storage and may play a major role in postharvest processes. Analysis of endo galactanase hydrolysates showed decreased portions of galactan-bound, terminal α-arabinopyranose units after storage. Therefore, these residues are most likely removed during postharvest galactan decomposition. The results of this study demonstrate the high complexity of neutral pectin side chains in apples and that pectic structural elements are differently prone to postharvest modifications.